(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Bhagavad Gita is a principles based text book of management. Being a good Leader, if we don’t encourage our team, those great ideas will be soon end. Teachings of Yoga helps person mentally empower with concentrate on their each duty. So yoga has been more important in professional field. Gita says - where we utilize the body it is called karma yoga. This makes it easy “Where there’s a will there’s a way”. Bhagavad Gita is based on a dialogue between Shree Krishna and Arjun mentioned in the ‘Bhishmaparva’ chapter of the epic ‘Mahabharat’ written by Vedavyasa. It is a divine text, which gives direction to live life with dignity and splendor. This paper aims to introduce the holistic vision of Leadership skills, which is described in the Bhagavad Gita. The Principles of Leadership is used in modern management field and also try to looks at how the Gita provides us the important tips of Leadership for organizations.